CORRELATION OF UCS, PLI, UTS, AND YOUNG'S MODULUS OF INTACT ROCK IN THE BARITO BASIN, SOUTH KALIMANTAN - Yohanes Indrastata, Raditya
The probability distribution for UCS, UTS, and Young’s Modulus has an important role in carrying out numerical modelling analysis for slope or tunnel stability using the finite element method (FEM). However, getting the right probability distribution for modelling does not take a short time because there are many processes to get this type of distribution. Therefore, a Fitting distribution is needed which is carried out using the Kolmogorov-Smirnov method to determine the correct distribution for each rock strength parameter and it is generally found that UCS, PLI, and E have a Log-normal distribution and UTS has a Weibull distribution. To obtain the correlation between UCS-E, UCS-PLI, and UCS-UTS, modelling was carried out using simple linear regression. The UCS-E correlation has a linear coefficient range of E = 100 – 140 MPa with a correlation value of 0.84 – 0.92. The UCS-PLI correlation has a linear coefficient range of UCS = 8 – 13 PLI with a correlation value of 0.78 – 0.95. The UCS-UTS correlation has a linear coefficient range of UCS = 7 – 10 UTS with a correlation value of 0.83 – 0.91. The results of simple linear regression were validated with the T-test, F-test, and normality test, as well as with previous research.